Sexual harassment: the extent of legal protection in education institution / Muaz Ahmad Khairuddin, Hezqin Mohd Raimi and Wan Mohd Azzrul Hisyam Wan Ab Aziz - Ahmad Khairuddin, Muaz; Mohd Raimi, Hezqin; Wan Ab Aziz, Wan Mohd Azzrul Hisyam (2009)
This research is conducted for studying the extent of legal protection on sexual harassment in education institution. This topic is chosen for the reason that it had been the issues of discussion on several grounds such as the absentee of the proper act that governs the act of sexual harassment, the closed cases in which the harasser was never brought to justice. Observations from various perspectives in order to support the finding of this research can be found in the first chapter until the fourth chapter. The finding of this research is seemed to favour the harasser on the grounds of inadequate protection in the laws in our country. Therefore, the last chapter will be concluded with several proposed amendments and new laws that are recommended to be implemented under the Act for the future benefits.